2009
DOI: 10.3233/nre-2009-0490
|View full text |Cite
|
Sign up to set email alerts
|

Treating underlying attention deficits as a means for improving conversational discourse in individuals with closed head injury: A preliminary study

Abstract: Background: It is documented that individuals with closed head injury (CHI) demonstrate difficulty with narrative and conversational discourse. Effective conversational discourse requires a complex interaction of linguistic, cognitive, and social abilities [6]. Reduced attention and concentration are among the most common cognitive sequela following CHI [39]. Aims: The present study investigated whether treatment of attention would facilitate conversational discourse for individuals with CHI. Two treatment pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…IPR capitalizes on authentic interpersonal interactions and footage is reviewed immediately afterwards, fostering identification of insights related directly to the interaction dynamics. This technique improved situational anxiety, overall self-concept, interpersonal communication skills, and specific behavior associated with effective interpersonal communication [54]. Further, the authors noted that participants experienced improvements in day-to-day interactions supporting generalization of skills developed through IPR.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…IPR capitalizes on authentic interpersonal interactions and footage is reviewed immediately afterwards, fostering identification of insights related directly to the interaction dynamics. This technique improved situational anxiety, overall self-concept, interpersonal communication skills, and specific behavior associated with effective interpersonal communication [54]. Further, the authors noted that participants experienced improvements in day-to-day interactions supporting generalization of skills developed through IPR.…”
Section: Introductionmentioning
confidence: 83%
“…Investigators found that joint intervention was superior to solo interventions, where addressing a jointly constructed conversation is less feasible. Youse and Coelho [54] used a similar video-review approach. In order to avoid a conversation that feels awkward or forced, interpersonal process recall (IPR) [54] is used to facilitate the interaction within guided review of videos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to adopt the episodic coordination to understand the meaning of the whole long sentences [1] [2]. Certainly, it is also necessary for narration of paragraph and story to use episodic coordination [19] [20] [21]. In computer simulation, classifying the sentence/paragraph into the episodic category of natural/social subjects like physics, biology, art, economy, and so on is designed to improve the comprehension of language [25].…”
Section: The Advantages Of Language Of Human Brainmentioning
confidence: 99%
“…Attention has focused on exploring the nature and extent of these difficulties, with the view to developing efficacious treatment methods (Galski et al 1998, Galvin et al 2010, McCarthy et al 2005. As cognitive-communication deficits arise from cognitive impairments following ABI, it is not surprising that treatment methods targeting cognitive and discourse skills independently have had limited success (Cannizzaro and Coelho 2002, Youse andCoelho 2009). The integrated treatment of related cognitive and discourse behaviours, as part of a broader approach that considers other psychosocial and emotional factors, may be a more prosperous approach to remediation , Yeates et al 2007, where clinicians are encouraged to design and implement holistic approaches to management and consider a wide variety of factors that influence social competence (Whyte 2014).…”
Section: Introductionmentioning
confidence: 99%